MENGIKIS MENTALITAS PRIYAYI DALAM PEMERINTAHAN - Haryatmoko Haryatmoko; Guno Tri Tjahjoko (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
The priyayi mentality has colored the behavior of the Indonesian government since the New Order era. Since the 1998 political reform, efforts to build government accountability have continued, but the practice of abuse of power has continued to grow. The purpose of this study was to examine the effectiveness of the National Movement for Mental Revolution in eradicating the culture of feudalism in government in Indonesia. The method of writing is done through literature review and case studies of government behavior. The results of this study indicate that: cases of corruption and abuse of power continue to occur and even increase; the culture of public service has not changed because it still places the public as an object, not a subject. The results of the study indicate the need to improve the mentality of public administrators, in addition to the need for a shift in the focus of public services from government to society or the public.